On maximum cycle packings in polyhedral graphs - Peter Recht; Stefan Stehling (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
This paper addresses upper and lower bounds for the cardinality of a maximum vertex-/edge-disjoint cycle packing in a polyhedral graph G. Bounds on the cardinality of such packings are provided, that depend on the size, the order or the number of faces of G, respectively. Polyhedral graphs are constructed, that attain these bounds.